Kepastian Hukum Wilayah Jabatan Notaris Sebagai Pemegang Protokol Notaris Yang Berakhir Masa Jabatannya - Ariawan, Putu Bellania (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 3 No 2 (2018)DO - 10.24843/AC.2018.v03.i02.p09, 2018)
A notary is permitted to have a position in only one city / regency, but in relation to his office, the authority he has is in all provinces of the city / regency. In relation to the notary's office area, there is still legal uncertainty and obscurity in the legal norms contained in the provisions of Article 63 paragraph (4) of the UUJN and its implementing regulations, namely Article 7 and 8 of the Republic of Indonesia Law and Human Rights Minister's Regulation Number 27 of 2016 concerning Position Formation Notary and Determination of the Category of Regions related to the formation of the position area for the appointment of the first Notary who also acts as the recipient of the Notary protocol which ends his term. This research is a normative legal research, with a legislative approach, using primary and secondary legal materials that are carried out through literature review techniques, then analyzed using description and interpretation techniques. The results showed that, there was still a vague norm by not explaining whether the notary who was first appointed and at the same time appointed as the protocol holder of the notary who had ended his term of office could automatically enter the retired notary working area. When referring to Article 8 of the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 27 of 2016 concerning Formation of Notary Position and Determination of Regional Categories, then the notary who is first appointed can only be domiciled in the specified regional category.